EXPLORATION OF THE INFLUENCE OF INTERNAL FACTORS OF TAXPAYERS ON TAX COMPLIANCE (CASE STUDY OF SELAYAR REGENCY) - Mediaty, Mediaty; Faqiha, A Nadya Nurul; Sari, Indira Puspita (Entrepreneurship Undergraduate Program at Amkop Business School, 2025)
This study aims to analyze the influence of taxpayer awareness, knowledge, and religiosity on taxpayer compliance in Selayar Regency. A quantitative method was used in this study, by collecting data through a questionnaire on 200 respondents who were individual taxpayers. The results of the study show that partially or simultaneously, the three independent variables have a positive and significant influence on taxpayer compliance. This research provides a practical contribution for tax authorities in designing strategic policies to improve tax compliance based on public awareness, knowledge, and religious values.Keywords: Tax Awareness, Tax Knowledge, Religiosity, Taxpayer Compliance